2022
DOI: 10.1073/pnas.2115799119
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational interaction of human EBP50 and ezrin overcomes masked binding site during complex assembly

Abstract: Multiprotein assemblages are the intracellular workhorses of many physiological processes. Assembly of constituents into complexes can be driven by stochastic, domain-dependent, posttranslational events in which mature, folded proteins specifically interact. However, inaccessibility of interacting surfaces in mature proteins (e.g., due to “buried” domains) can obstruct complex formation. Mechanisms by which multiprotein complex constituents overcome topological impediments remain enigmatic. For example, the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…2 B ). Peptide epitope mimetics (PEM) mimicking the N terminus of nascent proteins can abrogate cotranslational events ( 13 ). Moreover, the N-terminal 36 amino acids of AIMP2 are critical for its interaction with KARS1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 B ). Peptide epitope mimetics (PEM) mimicking the N terminus of nascent proteins can abrogate cotranslational events ( 13 ). Moreover, the N-terminal 36 amino acids of AIMP2 are critical for its interaction with KARS1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cotranslation targeting the N terminus of an emerging peptide to form a protein complex, as observed here, presents multiple advantages. A nascent, unfolded peptide can provide recognition sites that are masked in the mature, folded protein ( 13 ). Also, the frequent presence of a “translational ramp” in which rare codons in the first ∼50 N-terminal codons hinders translation and might facilitate protein folding ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezrin phosphorylation sites can be regulated by several signaling pathways and perform different physiological functions upon activation and phosphorylation ( Yin and Schnoor, 2022 ). Initial studies demonstrated that the critical T567 on C-ERMAD could be phosphorylated by Rho-kinase (ROCK) ( Ding et al, 2022 ), STE20-like protein kinase (SLK) ( Garland et al, 2021 ), lymphocyte-oriented kinase (LOK) ( Senju and Tsai, 2022 ) and protein kinase C(PKC) ( Khan et al, 2022 ) both in the laboratory and in living organisms. Ezrin Y145, Y353 and Y477 can be modified by phosphorylation through the action of Src kinases and the intrinsic Tyr kinase activity of receptors for epidermal growth factor, hepatocyte growth factor and Platelet-derived growth factor ( Huang et al, 2018 ; Derouiche and Geiger, 2019 ; Rainey et al, 2020 ).…”
Section: The Post-translational Modifications Of Ezrinmentioning
confidence: 99%
“…In the canonical co-translational mechanism, a mature, fully formed protein interacts with its partner, generally near the nascent N-terminal polypeptide, as it emerges from the exit tunnel of the ribosome. [1,2] In exceptions to this mechanism, both interacting polypeptides can be mRNA-bound, that is, in-cis, in which polypeptides emerging from the same mRNA interact, or in-trans where interacting polypeptides emerge from distinct translating mRNAs. Global investigations of complex assembly suggest a widespread process where 12 of 31 and 9 of 12 complexes in fission and budding yeast, respectively, appear to be assembled cotranslationally.…”
Section: Introductionmentioning
confidence: 99%